Assessment of River Habitat Quality in the Hai River Basin, Northern China - Ding, Yuekui (Int J Environ Res Public Health, 2015)
We applied a river habitat quality (RHQ) assessment method to the Hai River Basin (HRB); an important economic centre in China; to obtain baseline information for water quality improvement; river rehabilitation; and watershed management. The results of the assessment showed that the river habitat in the HRB is seriously degraded. Specifically; 42.41% of the sites; accounting for a river length of 3.31 × 10(4) km; were designated poor and bad. Habitat in the plain areas is seriously deteriorated; and nearly 50% of the sites; accounting for a river length of 1.65 × 10(4) km; had either poor or bad habitats. River habitat degradation was attributable to the limited width of the riparian zone (≤5 m); lower coverage of riparian vegetation (≤40%); artificial land use patterns (public and industrial land); frequent occurrence of farming on the river banks and high volumes of solid waste (nearly 10 m(3)); single flow channels; and rare aquatic plants (≤1 category). At the regional scale; intensive artificial land use types caused by urbanization had a significant impact on the RHQ in the HRB. RHQ was significantly and negatively correlated with farmland (r = 1.000; p < 0.01) and urban land (r = 0.998; p < 0.05); and was significantly and positively correlated with grassland and woodland (r = 1.000; p < 0.01). Intensive artificial land use; created through urbanization processes; has led to a loss of the riparian zone and its native vegetation; and has disrupted the lateral connectivity of the rivers. The degradation of the already essentially black rivers is exacerbated by poor longitudinal connectivity (index of connectivity is 2.08–16.56); caused by reservoirs and sluices. For river habitat rehabilitation to be successful; land use patterns need to be changed and reservoirs and sluices will have to be regulated.